Sipadantonius roihani gen. et sp. nov., a new genus and species of Pseudocyclopidae Giesbrecht, 1893 (Copepoda, Calanoida) from the marine cave “Turtle Tomb” of Sipadan Island, Sabah, Malaysia - Chaichat Boonyanusith; Koraon Wongkamhaeng; Abdul-Rahim Azman (ZooKeys)
A new genus and species of the family Pseudocyclopidae, Sipadantonius roihani gen. et sp. nov., was described based on specimens collected using a light trap in the marine cave of Sipadan Island, Sabah, Malaysia. The new genus is most related to Pinkertonius, primarily based on the similarity observed in the armament of ancestral segment IV of the male antennules, the armament of the female P5 Exp-3, the segmentation of the male P5, the armament of the maxillular basal exite, and the relative length of the ancestral segment XXVII of the antennules. Nevertheless, it distinguishes itself from Pinkertonius and all other genera of the family by the absence of the lateral seta of the basis of all swimming legs, the presence of an inner seta on the coxa of the female P5, the reduction of furcal setae I and III, as well as the specific armament of the ancestral segment XX of the antennules and the maxillular coxal endite. The female of Sipadantonius roihani gen. et sp. nov. has aesthetascs on the ancestral segments IV and XX of the antennules, as well as six setae on the maxillular coxal endite, exhibiting the most plesiomorphic characteristics of the family Pseudocyclopidae. The latter characteristic has not been recorded in the order Calanoida. It was hypothesised that the new species was a particle feeder living in the pelagic zone of the marine cave. The existence of the new species supported the assumption that the regional distribution of the family Pseudocyclopidae exhibited the Tethyan track, which might have been the subsequent result of the colonisation of the habitats prior to the closure of the Tethys Sea.